Langkah Awal Mengenal Penyakit Ginjal Kronis pada Lansia di Kota Padang - Anggraini, Debie; Adelin, Prima (Abdika Sciena, 2023)
The effect of changes in body fat percentage in the elderly will affect the estimation of glomerular filtration rate (eGFR) in the elderly. The aging process involves physiological and nutritional changes that will affect the nutritional status of the elderly, this will lead to malnutrition and overweight. Aging is associated with major changes in body composition, higher BMI is associated with improved survival in patients with CKD and very low BMI levels have been consistently associated with high all-cause mortality in the elderly. Higher BMI is associated with improved survival in patients on CKD and dialysis. By knowing changes in body composition through anthropometric measurements, it is expected to contribute to early detection of decreased kidney function or prevent the incidence of CKD in the elderly population.